Unmanned Aerial Vehicles An Introduction. - Garg, P. K. (Mercury Learning & Information, 2021)
Provides an overview of the basic concepts and components of UAVs, the various sensors used, architecture of autonomous UAVs, communication tools and devices to acquire real-time data, the software needed to analyse UAV data, rules and regulations to fly UAVs, application areas, and future areas of research.